(untitled) (Eurasian Journal of Ecology, 2016)
This study compared the distribution of genotypes and allele frequencies of gene FGFR2 (rs1219648) between breast cancer patients and the control group in the Kazakh and Russian ethnic groups. In contradistinction on a number of world populations associations of polymorphism in a site rs1219648 gene FGFR2 with breast cancer did not reveal neither in Kazakh, nor in Russian ethnic groups.